ANALISIS PENGARUH PERCEIVED PRICE DAN BRAND IMAGE TERHADAP REPURCHASE INTENTION PADA PRODUK AIR MINERAL VIT - Wahyuni, Reni Suci (House of Management and Business (HOMBIS) Journal, 2023)
This research aims to test and analyze the influence of Perceived Price and brand image on repurchase intention for Vit mineral water products. The population of this research is 100 consumers of Vit brand drinking water in Kebumen Regency. Data analysis techniques using descriptive and statistical analysis techniques include instrument tests (validity and reliability tests), classical assumption tests (normality test, heteroscedasticity test, multicollinearity test), multiple linear regression analysis, and hypothetical tests (partial t test, simultaneous F test, coefficient of determination) using the SPSS program. The results of the research show that Perceived Price and brand image have a positive and significant effect on repurchase intention, both partially and simultaneously.